Bioprocess development for enhanced spore production in shake flask and pilot scale bioreactors of bacillus thuringiensis var. Israelensis in submerged culture - Aziz, Ramlan (2015)
Bacillus thuringiensis subsp. Israelensis (Bti), has proven to be a safe and effective larvicide for controlling mosquito and black fly larvae. The effect of cultivation and bioproc ess development on Bti growth and sporulation was investigated in shake flask level and batch cultivation in the semi - industrial scale 16 - L stirred tank bioreactor. For industrial production of biocontrol microorganism, it is necessary to obtain high cell mass and spore production in a short time with low cost cultivation media. In this study, the new composition of production media was optimized which composed of (g L - 1 ): glucose, 10; yeast extract, 30; KH 2 PO 4 , 5; K 2 HPO 4 , 5; MgSO 4 . 7H 2 0, 0.005; MnSO 4 .H 2 O, 0.03; FeSO 4 , 0.01; CaCl 2 .7 H 2 O, 0.05; NaH 2 PO 4 , 1.5; NH 4 H 2 PO 4 , 1.5. The maximal cell dry mass and spore production, Spore max for shake flask study were 4.26 gL - 1 at 36 h and 3.29 ? 10 6 spore mL - 1 , respectively . Furthermore, studies of the cultivation conditio ns under controlled an d uncontrolled pH in the 16L - bioreactor wa s performed. The growth of Bti under uncontrolled pH cultivation showing decreased of glucose and total protein concentration in the media was correlated with the vegetative cell growth and sp orulation. The maximal cell dry mass and Spore max for uncontrolled pH bioreactor were 4.14 gL - 1 at 36h and 3.7 ? 10 6 spore mL - 1 , respectively . The maximal cell dry mass and spore production, Spore max for controlled pH bioreactor were 3.36 gL - 1 at 26 h and 3. 23 ? 10 6 spore mL - 1 , respectively . In conclusion, batch cultivation in 16 - L bioreactor with th e new optimized production medium under uncontrolled pH condition increased of the cell dry mass an d number of spores up to 23 % and 47 % , respectively.